Interleaved Bidirectional DC-DC Converter for Renewable Energy Application based on a Multiple Storage System - Mesalam, Yehya I.; Awdallh, Shaaban; Gaied, Hajer; Flah, Aymen (Engineering, Technology & Applied Science Research, 2024)
Due to its fewer components, the DC-DC three-phase converter has a simpler design and could be less expensive. However, it can present challenges in terms of precise voltage regulation and current balancing, due to the limited number of switching phases. On the other hand, the three-phase converter offers more precise voltage regulation and improved current balance owing to its higher number of phases. Although this results in increased design complexity and potentially higher cost, it allows for a more uniform distribution of current load among MOSFETs. The particular needs of the application, acceptable trade-offs between complexity, cost, and performance, as well as the requirement for precise voltage regulation and ideal current balancing, can determine which option is the best. This work investigates a three-phase interlaced DC converter with a parallel MOSFET. A two-way DC-DC converter was used to assess PWM when charging and discharging a battery. The results demonstrate a great DC voltage gain without a very high cycle load.